DRAFT GENOME SEQUENCE OF NONOMURAEA SP., A BACTERIA INHABITING BLACK TRUFFLE TUBER AESTIVUM FRUITBODY - Potapova N.A.; Dmitrieva M.E.; Malygina E.V.; Morgunova M.M.; Listopad A.S.; Lipatova O.E.; Emshanova V.A.; Martynova E.I.; Batalova A.A.; Axenov-Gribanov D.V. (Journal of Bioinformatics and Genomics)
Nonomuraea is a rare genus of Gram-positive aerobic bacteria belonging to actinobacteria. The genome sequence of novel Nonomurea sp. isolated from the truffle Tuber aestivum sample. The bacterial strain is genetically similar to N. glycinis and N. guangzhouensisis. We report this genome to accelerate investigation of the Nonomuraea genus for medical and biotechnological purposes, as well as exploration of species inhabiting T. aestivum fruitbodies. Assembly completeness of genome was 98.60%. GC content was 70.22% in consistency with Nonomuraea genus. The genome was annotated and predicted 9805 genes. The size of the genome is 10 Mb. We found clusters associated with polyketides, terpenes and NRP. Thus, the symbiotic organisms of truffle T. aestivum can be interesting and perspective object for biomedical and genetic engineering research.